Charting Sustainability: Triple Bottom Line (TBL) Analysis in The Palm Oil Supply Chain Landscape - Rabiatul Adwiyah; Yusman Syaukat; Heti Mulyati; Dikky Indrawan (Jurnal Manajemen dan Agribisnis, 2025)
Background: The industrial sector depends on a sustainable supply chain, which requires an organization to integrate (trade off) social, technological, economic, and environmental factors. One industry that applies the triple bottom line concept is palm oil. The palm oil industry is believed to have two drawbacks: harm to the environment, and social welfare. Sustainable supply chains have the potential to increase social welfare, reduce environmental impact, and increase profitability.  Purpose:  This study aims to enhance the understanding and implementation of sustainability in the palm oil supply  chain through three key objectives: (1) mapping current sustainability practices and performance across all supply chain actors; (2) analyzing limitations and inconsistencies in existing sustainability measurement methods, particularly in addressing the Triple Bottom Line (TBL) dimensions; and (3) developing standardized, practical, and theoretically grounded Key Performance Indicators (KPIs) to support consistent and transparent sustainability evaluation. Design/methodology/approach: The Matrix of Crossed Impact Multiplications Applied to a Classification (MICMAC) method was employed. This approach makes the strength of the correlation between the variables and secret to a more methodical and targeted solution more evident. Data were collected through surveys and in-depth interviews with 16 respondents, including managers, sustainability officers, and operational staff, across the palm oil supply chain. The research was conducted between August and December 2023 in North Sumatra, Indonesia, specifically in PTPN III and the Sei Mangkei Special Economic Zone (KEK Sei Mangkei).Conclusion: Based on the Matrix of Direct Influences (MDI) and the Matrix of Indirect Influences (MII), important variables significantly affect other variables. A MICMAC analysis was conducted to determine the critical elements in the sustainability of the palm oil industry supply chain. This analysis serves as the basis for the variables of industrial productivity, financial performance, access to price information, level of industry employee education, and availability of infrastructure.Originality/value (State of the art):  This study employs the Matrix of Crossed Impact Multiplications Applied to a Classification (MICMAC) method to identify key triple bottom-line indicators for implementing sustainable supply chains. Because Many sustainability studies focus on descriptive analysis or case comparisons, few apply a modeling approach that shows inter-variable influence and causal mapping, which enhances strategic decision making and improves the practical applicability of sustainability frameworks. Keywords: MICMAC method, sustainability, supply chain, palm industry